Characterization of the Mass-Transport Phenomena in a Superconcentrated LiTFSI:Acetonitrile Electrolyte. Issue 7 (1st January 2015) - Lundgren, Henrik; Scheers, Johan; Behm, Mårten; Lindbergh, Göran
Abstract : Superconcentration of aprotic electrolytes has recently emerged as a way to stabilize solvents that otherwise would be impossible to use, in e.g. lithium-ion batteries (LIBs). As demanding applications, such as hybrid electric vehicles and fast charging, become increasingly important, battery manufacturers are struggling to find a suitable electrolyte able to deliver high power with low polarization. Electrolyte characterizations able to accurately predict the high-power performance of such electrolytes are also of utmost importance. This study reports a full characterization of the mass-transport phenomena for a superconcentrated LiTFSI:acetonitrile electrolyte in concentrations ranging from 2.7 M to 4.2 M. The method obtains the ionic conductivity, cationic transport number, diffusion coefficient, and the thermodynamic enhancement factor, by combining mathematical modeling and three electrochemical experiments. Furthermore, the density and the viscosity were measured. The transport number with respect to the room is found to be very high compared to other liquid LIB electrolytes, but a low diffusion coefficient lowers overall performance. The ionic conductivity decreases quickly with concentration, dropping from 12.7 mS/cm at 2.7 M to 0.76 mS/cm at 4.2 M. Considering all the effects in terms of the mass-transport of the electrolyte, the lower end of the studied concentration range is favorable.